An update on Interleukin-9: from its cellular source and signal transduction to its role in immunopathogenesis - Chakraborty, Sushmita; Hieke-Kubatzky, Katharina; Mitra, Dipendra K. (International journal of molecular sciences, 2019)
Interleukin-9 (IL-9) is a pleiotropic cytokine and was primarily studied in the context of T helper 2 (TH2)-associated immuno-pathological conditions such as asthma and parasitic infections. There was a paradigm shift in the biology of IL-9 after the recent discovery of TH9 cells, a new subtype of TH cells which secrete IL-9 in copious amounts. This has resulted in renewed interest in this cytokine, which was neglected since discovery because it was considered it to be just another TH2 cytokine. Recent studies have shown that it has multiple cellular sources and is critically involved in the immune-pathogenesis of inflammatory diseases and in guarding immune tolerance. In this review, we will discuss its discovery, gene organization, cellular sources, and signaling pathways. Especially, we will give an update on the recent development regarding its relevance in the immune pathogenesis of human diseases.
Gesehen am 25.11.2019